Chimeric antigen receptor T-cell therapy for relapsed and refractory large B-cell lymphoma: A Canadian perspective (Canadian Hematology Today, 2022)
Comprising approximately 40% of diagnoses, lymphoma is the most common hematological malignancy in Canada, and 80% of lymphoma cases are non-Hodgkin lymphoma (NHL). Diffuse large B-cell lymphoma (DLBCL) accounts for approximately 30% of new NHL cases in Canada. First-line treatment with standard of care chemoimmunotherapy consisting of rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) results in a cure in approximately 60–70% of patients. Nevertheless, 30–40% of patients will experience relapse of their disease or are refractory to first-line therapy.Among those patients with relapsed or refractory DLBCL (R/R DLBCL), about 10–15% will exhibit primary refractory disease with either stable or progressive disease despite first-line therapy, while 20–25% will experience relapse after an initial response to treatment. Most relapses will occur within 2–3 years following initial treatment. For these patients, the standard approach is salvage chemotherapy followed by high-dose chemotherapy and autologous stem cell transplantation (ASCT) for those who meet the eligibility criteria and have chemosensitive disease.